Identification of clinician challenges in order to drive the development of competency-based education: results from an international needs assessment in multiple sclerosis - Sean M. Hayes; Mohammad Sharief; Pamela Ng (Journal of European CME, 2015)
Objective. To highlight clinical gaps of neurologists and nurses regarding their skills and confidence in engaging and communicating with multiple sclerosis (MS) patients to inform the design of continuing medical education (CME) initiatives. Methods. This international IRB-approved study deployed in six countries (France, Germany, Italy, Spain, UK and USA), utilised a mixed-methods approach (qualitative interviews and an online survey) to explore the self-reported challenges of neurologists and nurses across the spectrum of MS care. Results. The sample included actively practising neurologists (n=148) and nurses (n=146), 42% of whom had an annual caseload of 150+ MS patients. The participants reported challenges in assessing patients’ adherence to treatment, engaging patients in shared decision-making and communicating confidently with patients and caregivers. Participants reported their own skill and confidence deficits as potential causalities for these challenges. Conclusion. Results suggest that neurologists and nurses would be receptive to education to develop their skills with regard to communication with patients and caregivers. CME and performance improvement initiatives should address the clinical challenges identified in this study to optimise clinicians’ effectiveness and patient outcomes. Patient–provider communication skills represent a priority area for the development of CME and performance improvement initiatives.